ASSESSING THE CONSEQUENCES OF VEHICLE IMPORT BANS ON SRI LANKA’S AUTOMOBILE SECTOR AND BROADER ECONOMY - A.R.M Arshard; M.S.M Imthiyas (PT. Antis International Publisher, 2025)
Objective: This study evaluates the economic, industrial, and societal implications of vehicle import bans in Sri Lanka. It focuses on understanding their effects on local production, consumer behavior, employment, and macroeconomic variables. Method: Data were collected from stakeholders, including automobile dealers, industry experts, and policymakers. Analytical methods were used to identify trends in local production, consumer behavior, and employment impacts. Macroeconomic variables such as foreign exchange savings, inflationary pressures, and fiscal policies were also examined. Results: The findings reveal that the vehicle import ban has a dual impact. On one hand, it aids in foreign exchange conservation, aligning with broader economic objectives. On the other hand, it causes market contraction, reduces tax revenue, and creates industrial challenges, such as employment disruptions. Novelty: This research provides a nuanced perspective on the consequences of vehicle import restrictions in Sri Lanka. It bridges the gap between economic objectives and industrial sustainability, offering actionable insights for policymakers to balance these priorities effectively.